A Computerized Coding System for Processing Basic Histopathological Changes – Application to Vascular Pathology - Spagnoli, L. G.; Mauriello, A.; Sambuy, Y.; Bonanno, E.; Orlandi, A.; Palmieri, G. (Methods of Information in Medicine, 1986)
Among the numerous existing computer-based systems for processing pathological data, none contains sufficient space for encoding data on the basic cytological or histological changes of a certain organ or tissue, upon which the final diagnosis is based.An “analytical record” was constructed listing all the basic changes that can be encountered in the various pathological conditions of the vascular wall. The data collected on the “analytical record” were coded by means of an alphanumeric code and stored in an Apple II 48 K minicomputer.The advantages of this system include the computerization of the data by non-specialized personnel and the possibility to’ quantitatively analyze the histocytopathological parameters used for diagnosis in vascular pathology. This coding system may easily be adapted, with minor modifications, to the histopathological study of other organs and tissues.
Keywords: Minicomputer; Coding System; Histopathology; Vascular Pathology; Atherosclerosis